Taxonomic review of amphibians with emphasis on endemic species (Zoological Records and Reviews, 2022)
Amphibians represent one of the most threatened vertebrate classes globally, with endemic species bearingdisproportionate extinction risk due to their restricted ranges, specialised habitat requirements, and susceptibility toemerging infectious diseases. This review synthesises current taxonomic knowledge of endemic amphibians across fourglobally significant diversity hotspots -- the Western Ghats of India, the Atlantic Forest of Brazil, the mountains of theCameroon Highlands, and the highlands of New Guinea -- drawing on published literature, museum specimendatabases, and molecular phylogenetic studies published between 2000 and 2021. Across these four regions, 1,284amphibian species are documented, of which 847 (66.0%) are regionally endemic. The Western Ghats contributes 187endemic species including numerous recently described taxa in the families Nyctibatrachidae, Micrixalidae, andRanixalidae. The Atlantic Forest harbours the greatest absolute endemic richness (312 species), dominated by Hylidaeand Brachycephalidae. Molecular phylogenetic analyses across all four regions reveal consistent patterns of crypticspecies diversity -- with an estimated 20-35% of morphologically circumscribed species harbouring molecularly distinctlineages warranting species status. We assess the IUCN conservation status of all documented endemic species andidentify 284 (33.5%) as Threatened. The amphibian chytrid fungus Batrachochytrium dendrobatidis (Bd) and habitat lossare identified as the dominant threat drivers. Updated taxonomic recommendations and conservation priorities arepresented for each region.